Energetic Nitrogen‐Rich Polymers with a Tetrazene‐Based Backbone. (17th November 2020) - Eymann, John; Joucla, Lionel; Jacob, Guy; Raynaud, Jean; Darwich, Chaza; Lacôte, Emmanuel
Abstract: New energetic polymers were synthesized from monomers containing a trans ‐2‐tetrazene unit. In contrast to traditional binders, such as inert hydroxytelechelic polybutadiene or glycidyl azide polymers—in which the energetic features are on the side chains—the energetic groups in the polytetrazenes are incorporated directly in the polymer backbone. Thermal analyses demonstrated that decomposition occurs at approximately 130 °C, regardless of the polymer structure. Glass‐transition temperatures ranged from −34.2 to 0.2 °C and could be lowered further (to −61 °C) with the help of a new diazidotetrazene energetic plasticizer. Interestingly, hexafluoroisopropanol (HFIP) enabled complete, room‐temperature depolymerization within 1 week. This depolymerization should enable the recycling of unused pyrotechnic compositions based on these new binders. Abstract : Polytetrazenes with main‐chain tetrazene energetic moieties were obtained by the polycondensation of tetrazene monomers and diamines and released energy (up to 1790 J g −1 ) upon decomposition at about 130 °C. Their glass‐transition temperatures ranged from −61 to 0 °C, depending on the monomers and the presence or absence of a diazidotetrazene plasticizer. Hexafluoroisopropanol promoted depolymerization of the chains with the release of nitrogen (see scheme).